Crisis management communication and political communication in the age of social media: a case study of ZANU PF from 2015-2016 - Moyo, Ngqabutho M. (Midlands State University, 2018)
With the increase of people and usage of social media platforms intensification, so does the need for crisis management communication. This research focuses on how ZANU PF uses social media to control its Factional crisis post the Joyce Mujuru eras focusing on Twitter and Facebook as platforms for their public relations response to the political damaging series of events the party experienced from 2015-2016. Additionally, the study looks at how the social media users used Facebook and twitter as a platform to reach out to ZANU PF and air out their concerns on the series of crisis that the party experienced. A content analysis of posts and tweets written in response to the predicaments that befell ZANU PF through this it was developed that ZANU PF officials used the two social networks as a way to reach out and communicate on how the party was making things at the same time social media users from both ZANU PF members and from how opposition parties voiced negative opinions about Many other problems that were being caused by the plague of crisis in identifying how ZANU PF used social media and restoration strategies in the wake of the crisis, it is possible to compare their use to best practices that have developed through academic research and present case studies where social media and restoration strategy was used effectively. This can identify why ZANU PF officials’ responses where not well received. By ascertaining how social media users used Facebook and Twitter, it is possible to use this case study as an example of the importance of engaging with users and identifying areas of concern. This research has implications for politicians, public relations practitioners and all professionals who are charged with creating crisis communication plans. recommendations and Limitations of the study for upcoming research were included.